# What is the equation of the line normal to # f(x)=-sqrt((x-1)(x+3)# at # x=0#?

f(x) does not exist at x=0, hence normal to f(x) does not exist there.

By signing up, you agree to our Terms of Service and Privacy Policy

The equation of the line normal to f(x) = -sqrt((x-1)(x+3)) at x=0 is y = 0.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- What is the instantaneous rate of change of #f(x)=ln(2x^2-x+6) # at #x=-2 #?
- How do you find the equation of the tangent line to the curve #y=x-sqrtx# at (1,0)?
- How do you find the average rate of change of #y=(2x+1)/(x+2)# over [1,3]?
- The temperature T in #""^oC# of a particular city during a 24 hour period can be modelled by #T = 10 + 8 sin 12 pi t# where t is the time in hours, with t = 0 corresponding to midday. Find the rate at which the temperature is changing at 4pm.?
- How do you find the slope of the tangent line to the graph of #y = (ln x) e^x# at the point where x = 2?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7